(untitled) (Global Journal of Medical Research, 2015)
Spine is the most essential part of human body. Vertebrae and intervertebral discs are important parts of Spine. The Inter vertebral disc (IVD) is a complex and load bearing structure. IVD undergoes a process of change with age and leads to failures. This paper presents a novel model to detect IVD failures using Magnetic Resonance (MR) images. The proposed method makes use of Vertebrae Statistics description Algorithm (VESTAL) to create a template by extracting features from several MR images contains healthy IVDs. The proposed method measures IVD and vertebrae features like intensity, anterior width, posterior width and center length of IVD. A template is created by VESTAL algorithm by extracting feature from 220 healthy IVD images in this work. The proposed method is implemented on 45 case studies where IVD failure have taken place. Proposed method detected the failure region and classified the IVDwith 94% accuracy.